Reflection on health care from the philosophy of Martin Heidegger - Mazatán-Ochoa, Cecilia Ixel (2021)
Health care is inseparable from the person himself. However, just as each person has a different perspective on the world, so does this health care, which can come from oneself or from another (such as nursing staff). In such a way that in this individuality the importance of reflecting on health care is highlighted from the philosophy of Martin Heidegger, who through phenomenology will be able to reveal that care or Sorge revealed from the person himself, to build with this better specific health care, either provided by oneself (self-care) or by another being in the world (nursing).